FORMATION AND DEVELOPMENT OF INFORMATION SOCIETY IN THE CONTEXT OF ITS IMPACT ON QUALITY OF POPULATION LIFE - Panzabekova, A.Zh.; Mussayeva, D.M.; Zhanbozova, A.B. (Academic Journal of Physical and Chemical Sciences, 2018)
The aim of the work is to study the issues of the influence of the information society on the quality of life of the population. The goal set in the article was implemented using a systematic approach, methods of scientific abstraction, analysis and synthesis, comparison. The article substantiates the concept of the formation of the information society on the basis of a critical analysis of the most significant works on the issue under study. The study of existing different definitions of the concept of "information society" allowed the authors of the article to highlight the universal characteristics of the information society, recognized by all scientists in a certain measure. Particular attention is paid to the issues of the influence of information technologies on various spheres of human life. There are also nine main trends in the development of the modern information society, which were supported by real examples